Análise da regeneração do nervo isquiático de ratos em lesões moderadas e graves sob ação do laser de baixa intensidade - Benato, Davilene Gigo (Universidade Federal de São Carlos, 2010)
Peripheral nerves are frequently target of traumatic injuries and their functional recovery is generally incomplete. The aim of the present study was to evaluate the effects of 660 or 780 nm low-level laser therapy (LLLT) GaAlAs using different energy densities (10, 60 and 120 J/cm2) on nerve sciatic recovery after severe (neurotmesis) or moderate (axonotmesis) injuries in rat. One hundred and twenty eight Wistar male rats (275g) were divided into 16 groups, and they were performed as follow: For axonotmesis: Normal (N); axonotmesis (CR); axonotmesis and 660 nm LLLT with 10 J/cm2 irradiation (CR660 10J); CR660 60J; CR660 120J; CR780 10J; CR780 60J; CR780 120J. For neurotmesis: N; neurotmesis (TT); TT660 10J; TT660 60J; TT660 120J; TT780 10J; TT780 60J; TT780 120J. The LLLT irradiation was performed using a fix potence of 40 mW and a spot area of 4 mm2. Nerves submitted to axonotmesis or neurotmesis were irradiated with LLLT daily during 10 consecutive days starting on the first post-operatory. However, neurotmesis groups received additionally one month of LLLT applied every other day. Tibialis anterior (TA) muscles and sciatic nerve were evaluated 28 (axonotmesis) and 84 (neurotmesis) after surgery. The follow analyses were performed: muscle fiber, axon, myelin and nerve fiber cross-sectional area (CSA); matrix metalloproteinases (MMP) 2 and 9 activities; sciatic functional index; S-100 immunofluorescence. Data were submitted to homogeneity and normality tests. Anova one-way followed by Tukey tests and Kruskal-Wallis followed by Newman-Keuls tests were performed when data was parametric or non-parametric, respectively. Significance level was set at 5%. The results of the present study showed that groups irradiated with 660 nm LLLT with 10 or 60 J/cm2, and 780 nm 10 or 120 J/cm2 showed normal values of nerve fiber and myelin CSA. The 660 nm LLLT, regardless the energy density used, accelerated muscle fiber recovery and increased the MMP-2 activity in nerve. Furthermore, it also decreased the MMP-9 and MMP-2 activities in nerves and muscles respectively. All axotomized animals recovery normal levels of function on the 28 day after surgery. Regarding neurotmesis groups, TT660 120J presented higher values of myelin and nerve fiber CSA compared to TT. Superior values of muscle fiber CSA were observed in TT660 60 e 120J e TT780 10J compared to TT. These LLLT parameters were also efficient to decrease MMP-2 activity in TA muscles. All groups submitted to neurotmesis did not recover normal function after 84 days of injury. Based on the proposed objective, it is possible to conclude that LLLT, considering specific protocols vi of application, recovered nerves effectively, avoided muscle fiber atrophy and acted on the muscle and nerve extracellular matrix remodeling via MMPs regulation.
Keywords: Fisioterapia; Laserterapia; Axôniotmese; Neurotomia; Função neuromuscular; Metaloproteinase (MMP-2); CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL